2017
DOI: 10.5664/jcsm.6468
|View full text |Cite
|
Sign up to set email alerts
|

Awakenings? Patient and Hospital Staff Perceptions of Nighttime Disruptions and Their Effect on Patient Sleep

Abstract: Hospital staff and patients agreed that pain, vital signs and tests were top sleep disrupters. However, pain was associated with the greatest objective sleep loss, highlighting the need for proactive screening and management of patient pain to improve sleep in hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 19 publications
4
42
1
3
Order By: Relevance
“…To develop SIESTA, patients were surveyed, and focus groups of staff were conducted; overnight vitals, medications, and phlebotomy were identified as major barriers to patient sleep. 9 We found that physicians did not know how to change the default vital signs order "every 4 hours" or how to batch-order morning phlebotomy at a time other than 4:00 am. Nurses reported having to wake patients up at 1:00 am for q8h subcutaneous heparin.…”
Section: Development Of Siestamentioning
confidence: 85%
“…To develop SIESTA, patients were surveyed, and focus groups of staff were conducted; overnight vitals, medications, and phlebotomy were identified as major barriers to patient sleep. 9 We found that physicians did not know how to change the default vital signs order "every 4 hours" or how to batch-order morning phlebotomy at a time other than 4:00 am. Nurses reported having to wake patients up at 1:00 am for q8h subcutaneous heparin.…”
Section: Development Of Siestamentioning
confidence: 85%
“…Patients, clinical staff and hospital administrators share a growing awareness that sleep is severely disrupted among hospitalised patients, and this may represent an important target to improve recovery 31–33. Nonetheless, there remains a large gap between this awareness and the implementation of nocturnal sleep promotion protocols 31.…”
Section: Introductionmentioning
confidence: 99%
“…VS assessments are the second most common cause of sleep disruption in the hospitalized patient 16 , and safely reducing these interventions overnight can improve patient sleep quality and quantity while leading to better health outcomes. Multiple studies have measured the quality and quantity of sleep in hospitalized patients around the world, showing significant reductions in sleep quality for patients in North America 1,2,7 , Europe 17 , and Australia 18 , among others.…”
Section: Discussionmentioning
confidence: 99%